(untitled) (Journal Of Educational and Psychological Researches, 2017)
It is important to be able to be able to be able to do so. . (Physics and mathematics) English language lessons English language tutoring English language tutoring English tutoring of the Modern of the Modern of the Modern of the Modern of the Modern. English Artiques of the Imagisies of the Nature of the Sciences of the Sciences of the Confectionery of the Consulting of the Confectionery of the Consultants. Wikipedia. The current research objective has been to measure: - 1-The level of psychological and social harmony for the children of martyrs of the popular crowd. 2- the correlation between the psychological and social compatibility of the children of the martyrs of the popular crowd and its relationship to some variables. In order to achieve the objectives of the research, the psycho-social adjustment scale, prepared by Al-Janabi in 2002, was adopted. It consisted of (52) paragraphs divided into four main areas (self-compatibility, compatibility with parameters, compatibility with peers and compatibility with the system) (3, 2, 1) and the scale of (23) positive paragraph. The answer to the scale by the teachers because they are more in contact with children and spend more time with them, making the most confident and accurate measure of psychosocial compatibility in children. Since the standard used in the current research was built in a period of time earlier, it was therefore necessary to re-extract the factors of discrimination and honesty and stability of the scale. Where the scale was applied to a sample of children killed the popular crowd aged (4-6) years, where the size of (200) children and a girl after the extraction of honesty and stability for them. Through the results of the research was reached: - 1- The children of the father (the martyrs of the popular crowd) in the kindergartens are poor in their mental consensuses and agree with them as average compared to the children who do not miss the father. 2- The psychological and social compatibility of the children martyrs of the crowd did not differ on the degree of their (male - female). 3- What is the age of children in their compatibility with children, despite the small stage that they are going to adapt to the new situation on them, and this showed the index of compatibility, which appeared to engage with their peers who did not lose the father. Based on these results, a number of recommendations and proposals have been developed that can be utilized by educational and community institutions.